Zad 1
2 = 5
5ab = ab
-a2b2 = 3/4a2b2
Zad 2
a) -2a+2+8a-3a=3a+2
b) x-2y-6x-5y-2y=-5x-9y
c) 2x²-3y+5x+2y-x²=x²+5x-y
Zad 3
a) 7 x 8 - 1/2 x 8 = 56 - 4 = 52
b) 3 x 16 + 2 x - 4 = 48 - 8 = 40
c) (2 x 2 + 3 x -3)(5 - 2) = 3 x (4 - 9) = - 15
Zad 4
c
Zad 5
2b + 2 + 4b -1 + 2a + 3a + 1 = 6b + 5a + 2
Zad 6
a)
(4x - 2) - (3x + 4) = 4x - 2 - 3x - 4 = x - 6
b)
- 2x - (4 - x) + 2 = - 2x - 4 + x + 2 = - x - 2
c)
(2a - 4) + (2a + 4) = 2a - 4 + 2a + 4 = 4a
Zad 7
a)
3x + 2a - 3x² - 5a = - 3x² + 3x - 3a
b)
2a(a + b) - 2b(b - a) = 2a² + 2ab - 2b² + 2ab = 2a² + 4ab - 2b²
c)
(8x + 12)/4 - (7x - 7)/7 = 8x/4 + 12/4 - 7x/7 + 7/7 = 2x + 3 - x + 1 = x + 4
LICZE NA NAJ